Consolidation or cooperation: the future of EU development cooperation - Mikaela Gavas; Deborah Johnson; Simon Maxwell (Deutsches Institut für Entwicklungspolitik (DIE), 2010)
Two future paths are available for European development cooperation: either “cooperation”, in which the European Commission takes on the role of network coordinator and Member States take the lead in delivering aid; or “consolidation”, in which the EC plays a progressively larger role in shaping policy and delivering aid. The development agenda is evolving in a consolidationist direction, with a greater focus on collective solutions to global problems. However, the EU will find it difficult to move in this direction: the core conditions favouring greater consolidation, including the interests of Member States, do not appear to be met. A survey of development policy-makers confirms this view. There is enthusiasm for greater cooperation, but not for greater consolidation. The `quick wins' seem to be in the area of standard-setting and measures to improve aid effectiveness, rather than rebalancing between bilateral programmes and the EC.
Keywords: 330